2021
DOI: 10.1200/op.20.01050
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Systemic Therapy in Patients With Cancer Near the End of Life in the Pre- Versus Postimmune Checkpoint Inhibitor Eras

Abstract: PURPOSE: Systemic therapy use in the last 30 days of life (DOL) for patients with advanced cancer is a low-value medical practice. We hypothesized that systemic therapy use in the last 30 DOL increased after approval of antiprogrammed cell death protein 1 immune checkpoint inhibitors (ICIs) and has contributed to increased health care utilization and spending. METHODS: We investigated the change in prevalence of any systemic therapy use in the last 30 DOL among patients with advanced solid tumors in the 4 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Our findings reinforce the data generated by others describing increasing ICI utilization or high rates of ICI use near the EOL. [7][8][9][10][11][12] A recent study from 2019 found that ICI use at the EOL had increased significantly in those with poor ECOG PS but did not increase significantly in those with good ECOG PS. 12 In our study, over 50% of patients had a ECOG PS of $ 2, including 17% of patients with a ECOG PS of 3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings reinforce the data generated by others describing increasing ICI utilization or high rates of ICI use near the EOL. [7][8][9][10][11][12] A recent study from 2019 found that ICI use at the EOL had increased significantly in those with poor ECOG PS but did not increase significantly in those with good ECOG PS. 12 In our study, over 50% of patients had a ECOG PS of $ 2, including 17% of patients with a ECOG PS of 3.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Despite the widespread adoption of ICIs into clinical practice, only a few studies have investigated their use at the end of life (EOL). [7][8][9][10][11][12][13] While ICIs may be believed to be better tolerated in comparison with cytotoxic chemotherapy, the decision to use ICIs in those with advanced cancer often carries a degree of uncertainty for both patients and physicians. Predicting treatment response to ICIs is challenging because of variations by tumor type and limited reliability of biomarkers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Multiple studies have shown that ICI use near the end of life can also lead to negative outcomes, including delays in hospice referrals, more emergency department visits, hospital admissions, and more patients dying in the hospital. 13,[18][19][20][21] The promise of ICIs also leads patients with debility from cancer or other comorbidities to pursue rehabilitation near the end of life and hold on to hope for further therapy, although few successfully reach this goal. 22 These findings suggest that in pursuing ICI therapy with uncertain or low likelihood of benefit, patients and clinicians may defer important discussions about prognosis and patient preferences for end-of-life care and results in higher health care utilization.…”
mentioning
confidence: 99%